Pengaruh Kinerja Sosial Terhadap Profitabilitas Bank Syariah - Rosana Puspasari; Imron Mawardi (Universitas Airlangga, 2014)
This study aimed to investigate the effect of social performance to the profitability of sharia bank. This study uses quantitative approach with multiple regression analysis and four variables; they are Mudharabah-Musyarakah Financing, Qardh Financing, and Zakat as exogenous variables and Net income as endogenous variable.Based on findings, it revealed that Mudharabah-Musyarakah Financing and Zakat effect significantly positive to the net income of Sharia commercial bank. Meanwhile Qardh Financing has non-significantly effect to the net income of Sharia commercial bank. On the other hand, Musyarakah-Mudharabah financing, Qardh financing and Zakat simultaneously has significantly effect to the net income of Sharia commercial bank. REFERENCESAl-Jawziyyah, I.Q. 1995. I’lam alMuwaqqi’in. Kaherah.Almilia dan Wijayanto. 2007. Pengaruh Environmental Performance dan Environmental Disclosure terhadap Economic Performance. Proceedings The 1st Accounting Conference Depok.Antonio. 2001. Bank Syariah: Dari Teori Ke Praktik. Depok: Gema Insani danTazkia Cendikia.Astuti, Dewi. 2004. Manajemen Keuangan Perusahaan. Jakarta : Ghalia Indonesia.Carroll, A.B. 1979. A three-dimensional conceptual model of corporate social performance. Academy of Management Review,Vol. 4, pp. 97-505.Chapra, M. Umer. 2000. Sistem Moeneter Islam. Jakarta : Gema Insani Press dan Tazkia Cendikia.Clarkson, M. B. E. (1995). A Stakeholder Framework for Analyzing and Evaluating Corporate Social Performance. The Academy of Management Review.Departemen Agama RI. 2005. Al-Qur’an dan tafsirnya (Edisi yang Disempurnakan). Jakarta : Penerbit Lentera Abadi.Departemen Agama RI. 2005. Al Qur’an dan Terjemahan Al Jumaanatul’Alii. Bandung : CV Penerbit J-Art. Hameed et.al. 2004. Alternative Disclosure & Performance Measures for Islamic Banks. International Islamic University Malaysia.Iqbal, Zamir. 1997. Islamic Financial System, World Bank : Finance & Development. Kurniawan. 2010. Pengaruh Qardh terhadap Performa Bank Syariah Periode 2005:1-2008:12. Skripsi tidak diterbitkan. Surabaya Fakultas Ekonomi dan Bisnis Universitas Airlangga.Prawirosentono, Suyadi. 1999. Kebijakan Kinerja Karyawan. Yogyakarta : BPFERahman, A.R.A. dan Goddard, A. 1998. An Interpretive Inquiry of Accounting Practices in Religious Organisations. Financial Accountability and Management. Vol 14. No. 3. 184-190Ryandono, Muhammad. 2010. Peran dan Pengaruh Penghimpunan Dana dan Penyaluran dana serta Kinerja Bank terhadap Kesejahteraan Karyawan Bank Islam Perspektif Maqashid Syariah di Indonesia. Disertasi tidak diterbitkan. Surabaya Program Pascasarjana Universitas Airlangga.Samad dan Hassan. 2000. The Performance of Malaysian Islamic Bank during 1984-1997 : An explanatory study. International Journal of Islamic Financial Service. Vol. 1 No. 3.Samuelson, Paul A. dan William D. Nordaus. 2004. Mikro Ekonomi. Terjemahan. Jakarta : Erlangga.Sartono, Agus. 2001. Manajemen Keuangan Teori dan Aplikasi. Yogyakarta : BPEF-YOGYAKARTA.Tangkiisan, Hessel Nagi S. 2005. Manajemen Publik. Jakarta: Gramedia Widia.